The Influence of Family Centered Care Against Quality Life of Stroke Patient at Home in Tomohon City Indonesia - Sumakul, Vione Deisi Oktavina; Karouw, Brigita Maria; Pongantung, Henny; Langingi, Ake Royke Calvin (East Asian Journal of Multidisciplinary Research, 2024)
Stroke is a neurological condition that can lead to death, physical and mental impairment, and even premature death. It is important to understand the changes that occur in the early stages of a stroke as they contribute to cell damage at the time of the stroke. It is vital to undertake self-intervention that is expected to improve healing, quality of life, hospitalization time, and stroke mortality.. The aim of this study was to analyze the influence of family centered care against quality life of stroke patient at home in Tomohon City, Indonesia. The method used was pre-experimental with a pre-post test design with a sample of 150 patients stroke using the Wilcoxon test. The sampling technique uses non-probability. The instruments were used questionaire about family care centered for patient stroke. The research results obtained a value of p = 0.001 < α = 0.05, stating that there was an influence of family centered care on stroke patient care at home in Tomohon City. The conclusion in this study is that level of family centered care on stroke patient care must be increase at home in Tomohon City to reducing level of stress. It is because family centered care on stroke patient increase quality of life patient stroke.